Comparison of choroidal thickness in systemic hypertensive subjects with healthy individuals by spectral domain optical coherence tomography - Shalaka R Waghamare; Sunita Mittal; Monika Pathania; Ramanuj Samanta; Devesh Kumawat; Neeti Gupta; Sanjeev K Mittal (Indian Journal of Ophthalmology, 2021)
Purpose: The purpose of the study was to compare the choroidal thickness in normal population and hypertensive patients and to assess the possible effect of hypertension on choroidal thickness using Spectral Domain Optical Coherence Tomography (SD-OCT). Methods: This was a comparative cross-sectional study. A total of 68 eyes of 34 individuals in the age group of 40–60 years were included in both the hypertensive group and control group. Individuals with refractive error beyond ± 3 D and posterior segment pathology were excluded. The choroidal thickness was measured at the sub-foveal region, 500 μm nasal and 500 μm temporal to the fovea on SD-OCT with enhanced depth imaging (EDI) mode. Systolic blood pressure (SBP), Diastolic blood pressure (DBP), and Mean arterial pressure (MAP) were recorded in all individuals. Duration of hypertension was also noted in hypertensive individuals. Results: The choroidal thickness at all locations was significantly lower in the hypertensive group (subfoveal, nasal, temporal and mean choroidal thickness 253.24 ± 63.96 μm, 249.35 ± 63.57 μm, 250.01 ± 63.37 μm, 250.87 ± 63.38 μm, respectively) as compared to the control group (subfoveal, nasal, temporal and mean choroidal thickness 301.25 ± 55.79 μm, 298.97 ± 57.07 μm, 299.49 ± 55.06 μm, 299.90 ± 55.50 μm, respectively). The choroidal thickness in the hypertensive group also had a significant negative correlation with the SBP (Spearman correlation coefficient, rho = –0.35, P = 0.003) and the duration of hypertension (rho = -0.25, P = 0.037). Conclusion: The study demonstrated decreased choroidal thickness in systemic hypertensive subjects as compared to age-matched healthy individuals. The choroidal thickness in hypertensive subjects also had a significant but weak negative correlation with SBP and duration of hypertension.